2016
DOI: 10.1002/2016jf004093
|View full text |Cite
|
Sign up to set email alerts
|

Reply to comment by Iverson on “The reduction of friction in long runout landslides as an emergent phenomenon”

Abstract: Here we address the comments by Iverson (2016) on our recent work concerning the reduction of friction in long runout landslides. Iverson (2016) questions the veracity of our models and suggests that high basal pore fluid pressure is the dominant mechanism reducing friction in long runout landslides. The main goal of our work was to elucidate the mechanism responsible for the apparent reduction of friction and long runout occurring in the landslide simulations of Campbell et al. (1995), which did not include a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…Recent studies of debris avalanches have indicated the necessity of the normal stress reduction in debris avalanches (Pudasaini & Miller, 2013), which is also supported by experimental (R H Iverson, 1997;R M. Iverson & Vallance, 2001) and numerical (Gueugneau et al, 2017;Iverson et al, 2015;Lucas et al, 2014) studies. Nevertheless, this is currently the source of active debate (Davies & McSaveney, 2016;Iverson, 2016;Johnson et al, 2016aJohnson et al, , 2016bJohnson et al, , 2016c.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of debris avalanches have indicated the necessity of the normal stress reduction in debris avalanches (Pudasaini & Miller, 2013), which is also supported by experimental (R H Iverson, 1997;R M. Iverson & Vallance, 2001) and numerical (Gueugneau et al, 2017;Iverson et al, 2015;Lucas et al, 2014) studies. Nevertheless, this is currently the source of active debate (Davies & McSaveney, 2016;Iverson, 2016;Johnson et al, 2016aJohnson et al, , 2016bJohnson et al, , 2016c.…”
Section: Discussionmentioning
confidence: 99%
“…Water plays an important role for the amount and rate of entrainment and erosion (Iverson and Ouyang, 2015). Especially for rock avalanches traveling on ice (Huggel et al, 2008;Deline et al, 2015;Bessette-Kirton et al, 2018;Walter et al, 2020) or wet, soft sediments (e.g., lake sediments, Figure 2E), the increased pore pressure enhances the scour of the bed, reduces basal friction and causes velocity, mass and momentum to increase (Iverson et al, 2011;Iverson, 2016;Johnson et al, 2016). Pure ice has a basal friction which is about 75% lower than that of pure rock.…”
Section: Erosion/entrainment/role Of Watermentioning
confidence: 99%